Ileocolic Mucormycosis – an Unusual Cause of a Mass in the Right Iliac Fossa - Kishanchand Chethan; Seetharam Prasad; Lingadakai Ramachandra (Canadian Journal of Infectious Diseases and Medical Microbiology)
Mucormycosis is a relatively uncommon, aggressive and lethal mycosis. Fungi from the order Mucorales are the etiological agents of mucormycosis. The condition is more common among the immunocompromised, diabetic patients with ketoacidosis and people with iron overload syndromes. Diagnosis of mucormycosis requires a high index of suspicion regarding the possibility of the condition in high-risk individuals. Timely diagnosis is critical to survival and minimization of morbidity. A favourable outcome is possible only if appropriate treatment is initiated as early as possible. The present article reports a case of ileocolic mucormycosis involving a patient with chronic renal failure and familial hyperuricemia.